Lean six sigma and sustainability in the energy sector: A state of the art review - Subramaniam, Sharmelen; Norazlianie, Sazali; Afdhal, Junaidi; Noor Azizah, Sidek; Kadirgama, Kumaran (Penerbit UMP, 2026)
The energy industry is particularly put under pressure to enhance the efficiency of its operations and at the same time maintain high targets in sustainability and decarbonization. Lean Six Sigma (LSS) as a systematic approach to combine waste minimization with variation control has become a promising operating scheme to overcome these issues. The narrative review is a synthesis of the current research on the use of LSS in the energy sector and specifically on its environmental, economic, and social sustainability consequences. The review follows the development of LSS since its beginning with traditional energy operations through the growth of its application in renewable energy systems and utilities, and smart grids. It is always evident that LSS has the potential to bring quantifiable results, such as energy conservation, emission cuts, cost effectiveness, increased asset durability, and worker safety through operational strategies, by integrating sustainability goals into the workplace. One of the current trends that have been pointed out in the literature is the integration of LSS with computer technologies, including Industry 4.0 tools, real-time monitoring, artificial intelligence, and digital twins, which enhance the work on data-driven decision making and scale improvement. Irrespective of these benefits, structural, organisational, and regulatory impediments continue to curtail its implementation even in complicated resource-hindered environments. This review makes LSS a critical interaction point between sustainability and efficiency by defining patterns of application, its effect on sustainability, and implementation issues. It also provides.